Does Management Support Matter in Elucidating the Linkage of Individual Characteristics and e-Learning Acceptance? - Sutrisno Hadi Purnomo; Tur Nastiti (Asian Academy of Management Journal, 2019)
This study attempts to examine the hypothesis that management support elucidates the relationship between individual characteristic and e-learning acceptance factors including perceived ease of use and perceived usefulness. Quantitative methodology was used in this study through survey. This study collects 306 usable questionnaires from employees of Indonesian banking industries with experience in e-learning courses. The study uses descriptive statistical data and hierarchical regression analysis. The hypotheses on individual characteristics and acceptance factors relationships were generally accepted. Management support was found to positively contribute to e-learning acceptance. Management support has also showed its importance in elucidating the relationship between tangible individual characteristics and e-learning acceptance. However, the findings show limited supports of the moderating influence of management support. Management support, in terms of consideration, policy, and facilities were valuable in developing an appropriate acceptance of e-learning application in a company. Management support shows the managers’ commitment and assurance of e-learning benefits thus strengthening employees’ willingness to use e-learning, especially for those who previously experienced in using technology-based devices. This study contributes new knowledge to the existing body of literature on e-learning adoption research by providing a more complex view of e-learning adoption.